Effect of Probiotic Lactobacillus sp. Dad13 on Humoral Immune Response of Balb/C Mice Infected with Salmonella typhimurium - Ika Dyah Kusumawati; Eni Harmayani; Widya Asmara (Indonesian Journal of Biotechnology, 2006)
An indigenous strain of lactic acid bacterium (LAB) identified as Lactobacillus spp. Dad13 (Dad13), isolated from traditional fermented buffalo milk, was found to be potential as probiotic. The aim of this research was to study the effect of probiotic Dad13 on humoral immune response of Balb/C mice infected with Salmonella typhimurium. The specific objective was to find out the effect of different Dad13 consumption time (before and along with infection of S. typhimurium) on the humoral immune response of Balb/C mice. The experiment was conducted by in vivo trial on 20 males of Balb/C mice, age of 6-8 weeks, fed with AIN-93 standard diet. The mice were assigned into 4 groups. Each group received the following treatments, ie. Dad13 only, Dad13 before infection, Dad13 along with infection and Salmonella infection only. A volume of 100 µl Dad13 cell suspensions (1010  CFU/ml) were given by oral forced feeding daily for a week, at week 3 for group before infection and at week 4 for group of Dad13 only and Dad13 along with infection. Salmonella infection (109   CFU/ml) was given once orally at week 4 to all groups except group treated with Dad13 only. The humoral immune response of Balb/C mice was detected 2 weeks after infection by measuring the titers of IgG and IgA specific from serum and mucosal intestinal liquid samples using Enzyme-linked Immunosorbent Assay (ELISA) method. The result indicated that humoral immune response of Balb/C mice consuming Dad13 before and along with Salmonella infection were significantly different (p<0.05). Dad13 consumption along with Salmonella infection increased circulated IgG and IgA as well as secretory IgA. It can be concluded that Dad13 probiotic feeding along with infection increased humoral immune response more significantly compared to that before infection.